Evidence for the Involvement of the Dopaminergic System in Seizure and Oxidative Damage Induced by Tramadol. (March 2018) - Bameri, Behnaz; Shaki, Fatemeh; Ahangar, Nematollah; Ataee, Ramin; Samadi, Mahedeh; Mohammadi, Hamidreza
Tramadol (TR) is a synthetic analgesic drug with central function that can induce seizures even at therapeutic doses. The exact mechanism of TR effect on seizure generation is not clear, but inhibition of the serotonin and nitric oxide pathways and inhibitory effects on GABA receptors are the most common hypotheses about the seizure-inducing mechanism of the TR. This study aimed to evaluate the role of dopaminergic system on the seizure and oxidative damage induced by TR using agonist and antagonist drugs of this system in the Albino mice. Clonic seizure induced by TR was evaluated as seizure threshold. Haloperidol (0.2 mg/kg, IP), a predominantly D2 receptor antagonist, and cabergolin (0.5 mg/kg, IP), a dopamine agonist specific for the D2 receptors, were injected 60 minutes before the seizure induction. The seizure threshold was significantly increased by dopaminergic antagonist, but it was decreased significantly by pretreatment with the selective agonist. Oxidative stress biomarkers (reactive oxygen species, lipid peroxidation, and protein carbonyl content) significantly increased and glutathione content significantly decreased in brain mitochondria by TR compared with the control group, whereas oxidative markers were decreased significantly after pretreatment with haloperidol compared with the TR group. This study revealed that the dopaminergic system is involved in TR-induced seizure, and meanwhile, inhibition of dopamine D2 receptors can increase the TR threshold seizure and decrease the oxidative damage in the brain mitochondria. Conversely, stimulation of dopamine D2 receptors by cabergolin can decrease the TR threshold seizure and glutathione content in the brain mitochondria.